Vascular Supply to the Femoral Head in Patients With Healed Slipped Capital Femoral Epiphysis. Issue 1 (January 2020) - Shore, Benjamin J.; Mardam-Bey, Sami W.; Kim, Young-Jo; Matheney, Travis; Novais, Eduardo N.; Millis, Michael B.; Yen, Yi-Meng
Abstract : Background: Slipped capital femoral epiphysis (SCFE) is one of the most common hip disorders. The vascularity of the lateral epiphyseal vessels supplying the femoral head in patients with healed SCFE has not been well defined. The purpose of this study was to characterize the location and number of lateral epiphyseal vessels in young adults with healed SCFE. Methods: This was a retrospective study of 17 patients (18 hips) with a diagnosis of SCFE and a matched control group of 17 patients (17 hips) with developmental dysplasia of the hip. All patients underwent high-resolution contrast-enhanced magnetic resonance imaging to visualize the path of the medial femoral circumflex artery and the lateral epiphyseal arterial branches supplying the femoral head. Results: There were 5 unstable SCFEs and 13 stable SCFEs with an average slip angle of 31 degrees. (All patients had been treated with in situ pinning and screw removal). Average age at time of magnetic resonance imaging was 24.5 years (range, 15 to 34 y). The lateral epiphyseal vessels reliably inserted on the posterior-superior aspect of the femoral neck from the superior-anterior to the superior-posterior position in both the SCFE and control groups. An average of 2 (±0.8) retinacular vessels were identified in the SCFE group compared with 5.2 (±0.7) retinacular vessels in the control group ( P <0.001). Conclusions: In healed SCFE, the lateral epiphyseal vessels reliably insert in the same anatomic region as patients with hip dysplasia; however, the overall number of vessels is significantly lower.